CAGE13-7 Cruise Report: Gas Release Activity & Underwater Landslide Research Cruise - Mienert, Jürgen; Plaza-Faverola, Andreia; Johnson, Joel; Franek, Peter; Urban, Peter; Osti, Giacomo; Iversen, Steinar; Nair, Anoop; Olsen, Bjørn-Runar (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
The overall aim of the CAGE 13-7 cruise was to study the gas release activity from gas hydrated sub-seabed environments at the continental margin off Svalbard towards the Norwegian-Greenland Sea and Arctic Ocean. Acoustic measurements in the water column, water sampling for gas analyses, seismic profiling, bathymetry mapping, and sediment coring allowed to reach this aim. Generally, the water column above gas flares may be rich in methane but methanotrophic microorganisms might hinder an escape of methane from the water to the atmosphere. At the Molloy transform and the Vestnesa ridge we collected seismic data and sediment cores for sampling gas hydrates. We also took sediment cores from a submarine slide complex at the continental margin of NW Svalbard. The age of this slide is of interest because it sits on gas hydrated sediments as indicated by a BSR. The timing of the slope failure is unknown. At the massive Hinlopen slide area we surveyed the eastern sidewall, the toe of the slope and a block within the major slide debris flow area to understand better a potential coupling between slide processes and gas hydrates. Seismic profiles show bottom simulating reflectors that are indicative for gas hydrate underneath the southeastern headwall of this slide complex. The cruise may be known as: CAGE13_JM